Pengaruh Insentif dan Pengembangan Karir terhadap Kepuasan Kerja melalui Kinerja Karyawan sebagai Variable Intervening/Moderating pada AJB Asuransi Bumiputera 1912 Palembang - Anton Kurniawan (Universitas Negeri Yogyakarta, 2016)
Effect of Incentives and career development to job satisfaction over the performance of the employee as an intervening variable in the Company of AJB Bumiputera 1912. This study aims to identify and analyze the influence of variable incentives and career development directly and indirectly, on the performance and job satisfaction in of AJB Bumiputera 1912 Palembang. Research sample of 120 people conducted a census by using Structural Equation Model (SEM) to analyze the data using LISREL software. The results showed the effect of incentives on job satisfaction of 0.21, while the career development of only 0.13, meaning that incentives have a greater influence on job satisfaction of the career development. The results of calculation of the direct influence of performance, incentives and career development to job satisfaction can be concluded that the performance had the greatest direct influence on job satisfaction (0.26) of the direct influence of incentives and career development, each of which only 0.21 and 0.13. While the indirect effect of incentives and career development to work through performance pepuasan shows that incentives have indirect influence greater (0.06) than in the career development (0.04). To improve job satisfaction in insurance AJB Bumiputera 1912 Palembang, needs to be improved incentives through bonuses, commissions or social security for employees who excel and enhance career development by providing a variety of opportunities to grow.